Morality for beautiful girls (No. 1 Ladies Detective Agency, 3,, 2003)
Fans around the world adore the bestselling No. 1 Ladies’ Detective Agency series and its proprietor, Precious Ramotswe, Botswana’s premier lady detective. In this charming series, Mma  Ramotswe—with help from her loyal associate, Grace Makutsi—navigates her cases and her personal life with wisdom, good humor, and the occasional cup of tea.   In Morality for Beautiful Girls, Precious Ramotswe, founder and owner of the only detective agency for the concerns of both ladies and others, investigates the alleged poisoning of the brother of an important “Government Man,” and the moral character of the four finalists of the Miss Beauty and Integrity Contest, the winner of which will almost certainly be a contestant for the title of Miss Botswana. Yet her business is having money problems, and when other difficulties arise at her fiancé’s Tlokweng Road Speedy Motors, she discovers the reliable Mr J.L.B. Matekoni is more complicated then he seems.

Miss Julia's school of beauty (Miss Julia, 6,, 2006)
Imagine Aunt Bee from The Andy Griffith Show with a lot more backbone and confidence," wrote Publishers Weekly about Miss Julia, Ann Ross's endearing Dixie doyenne of decorum. Don't miss her latest, Miss Julia Raises the Roof, coming April 2018 from Viking. In her latest romp, Miss Julia—now Mrs. Sam Murdoch—returns from her whirlwind elopement, only to find herself roped into Hazel Marie's scheme to raise money by throwing a beauty pageant. Though it all seems a tad distasteful, it's nothing compared to the revelation that Pigeon Forge, the marriage mill across the state line that wedded Julia and Sam, might not be legitimate. And a flustered Julia can't help wondering whether she and Sam can keep up appearances before the town finds out they might be living in sin.

Sour grapes (Savannah Reid mystery, 6,, 2004)
When it comes to sassy private detectives, no one's bigger than Savannah Reid. The feisty, full-figured, steel magnolia of G. A. McKevett's acclaimed mysteries knows how to turn every investigation into a delicious romp, even when she's dealing with a bunch of waif-like beauty queen hopefuls who will kill to be crowned. . . Sour Grapes Things finally seem to be calm and peaceful in Savannah's life, but before she can celebrate by biting into a mouthful of juicy fried chicken, her spoiled baby sister, Atlanta, comes knocking. Atlanta's determined to become a star, and her first step is the Miss Gold Coast Beauty Pageant that's being held right in San Carmelita. Savannah is feeling pretty ornery about the impromptu visit, but she's more alarmed about Atlanta's growing obsession with her appearance. Savannah blames it all on the beauty pageant, where the competition has become so fierce that someone's been driven to murder. Desperate to keep her flighty sister out of harm's way, Savannah digs into a real beauty of a case--and discovers the ugly underside of the wave-pose-and-cry scene. And when it comes to a bevy of backstabbing, sequin-wearing, crown-coveting glam girls, the question isn't who would want to commit murder, but who wouldn't?

Death by tiara (Jaine Austen mystery, 13,, 2016)
"When she is hired to write lyrics for a contestant in the talent competition for the Miss Teen Queen America pageant, freelance writer Jaine Austen is plunged into a glittering nightmare of vicious stage moms, exacting judges and trash-talking teens after a catfight turns deadly"--

The Tiara Club (St. Martin's Publishing Group, St. Martin's Griffin, 2005)
Grab your sparkliest tiara, blend your favorite fruity drink, and get ready to laugh and cry with the women of the Tiara Club. Georgia Elliott grew up in a small Gulf town full of Southern charm, and a superefficient grapevine, so the few secrets she's managed to keep are precious, including that she invented TV's hottest new kitchen gadget, the Miracle Chef. A second-generation beauty queen, Georgia turns to women she knows she can trust to keep her secret from her controlling society mama: the Tiara Club. All the members are veterans of the pageant circuit, but they've just admitted one woman who doesn't fit in, a Yankee, who's never taped her breasts or smeared glue on her butt to wow the judges. And, this year the Tiara Club is determined to help this outsider win the coveted Shrimp Queen crown. Add in an impending wedding and the club's attempts to keep Georgia's secret, and the women of the Tiara Club have to do all they can to hold on to their poise, their friendships, and their senses of humor.

Sugar and iced (Cupcake Bakery Mystery, ,, 2017)
Normally Melanie Cooper and Angie DeLaura wouldn't be caught dead at a beauty pageant, but when Mel's mom asks them to provide cupcakes for the seventy-fifth annual Sweet Tiara contest as a favor for her best friend, they can't say no. Plus between cooking up a daily display for the three-day event and sponsoring a cupcake creation challenge for the participants, Fairy Tale Cupcakes will get great publicity. But the world of pageants is even hotter than Mel's kitchen. A high-strung judge and a pushy stage mom target Lupe, a young friend of Mel and Angie's, at the competition and aim to take her out--by any means necessary. When the same judge shows up dead underneath Mel and Angie's cupcake display, Lupe is crowned the lead suspect. Now Mel and Angie will have to find the real killer quickly or Lupe may be strutting the catwalk in prison pinstripes...

Bone appetit (Sarah Booth Delaney, ,, 2011)
In the midst of a cook-off at a posh spa in Mississippi, southern PI Sarah Booth Delaney gets embroiled in a juicy murder when the beauty contest/cook-off's top contender gets poisoned.

Beauty queens (Scholastic Inc., Scholastic Press, Scholastic Audiobooks, 2011)
When a plane crash strands thirteen teen beauty contestants on a mysterious island, they struggle to survive, to get along with one another, to combat the island's other diabolical occupants, and to learn their dance numbers in case they are rescued in time for the competition.

The accidental beauty queen (Center Point Large Print, Simon & Schuster Audio, Gallery Books, 2019)
"Sometimes being pushed out of your comfort zone leads you to the ultimate prize. Charlotte and Ginny Gorman might look alike but they're completely different in every other way. Bookish Charlotte loves her job as an elementary school librarian, while her twin sister is an Instagram-famous beauty pageant contestant. Ginny has been chasing a crown since she was old enough to enunciate the words world peace, and she's not giving up until she's crowned Miss American Treasure. Dragging Charlotte to the pageant with her for good luck, Ginny's winning plan goes awry when she has a severe allergic reaction to dinner the night before the competition. A trip to urgent care confirms that she won't be back in beauty queen form for at least three days. After a few tears and a whole lot of begging, Charlotte agrees to take her sister's place in the pageant. Overnight, she's thrown into the glittery world of hair extensions, false eyelashes, and push-up bras. Charlotte realizes that there might be more to the pageant circuit than just a sparkly crown." -- Bookish Charlotte Gorman loves her job as an elementary school librarian, while her twin Ginny is an Instagram-famous beauty pageant contestant. Ginny is not giving up the circuit until she's crowned Miss American Treasure, and drags Charlotte to the pageant for good luck. When Ginny has a severe allergic reaction to dinner the night before the competition, she won't be back in beauty queen form for at least three days. After a few tears and a whole lot of begging, Charlotte agrees to take her sister's place in the pageant-- and comes to realize that there might be more to it than just a sparkly crown. -- adapted from back cover.

Brooke (Orphans, 03,, 1998)
When Brooke is adopted by a wealthy couple, she thinks her life will be perfect, but when her mother starts molding Brooke into a pint-sized version of herself, she realizes that her mother didn't want a daughter, she wanted a clone.

Boardwalk summer: a novel (HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollins Publishers, 2018)
"Two young women two generations apart discover the joy and heartbreak of following their dreams. Aspiring Hollywood actress Violet makes a shocking choice in 1940, and seventy years later, Mari sets out to discover what happened on that long ago summer. Santa Cruz, Summer 1940: When auburn-haired Violet Harcourt is crowned Miss California on the boardwalk of her hometown, she knows she is one step closer to her cherished dream: a Hollywood screen test. But Violet's victory comes with a price--discord in her seemingly perfect marriage--and she grapples with how much more she is willing to pay. Summer 2007: Single mother Marisol Cruz lives with her parents in the charming beach cottage that belonged to her grandfather, Ricardo, once a famed performer on the Santa Cruz Beach Boardwalk. Drawn to the town's local history and the quaint gazebo where her grandparents danced beneath the stars, Mari sells raffle tickets at the Beach Boardwalk Centennial Celebration, and meets Jason, a California transplant from Chicago. When Mari discovers the obituary of Violet Harcourt, a beauty queen who died too young, she and Jason are sent on a journey together that will uncover her grandfather's lifelong secret--his connection to Violet--a story of tragedy and courage that will forever transform them." --

Mr. & Mrs. American Pie (Inkshares, Inc, Inkshares, 2018)
"The year is 1969. Dick Nixon was just sworn in as the thirty-seventh President of the United States. Neil Armstrong just took one small step for man and one giant leap for mankind. And notable Palm Springs socialite Maxine Simmons just found out that her husband is leaving her for his twenty-two-year-old secretary. After a public meltdown at Thanksgiving, Maxine finds herself not only divorced but exiled to Scottsdale, Arizona. However, these desert boondocks will not be her end--only her Elba. The former beauty queen sets her eyes on a new crown: that of the Mrs. American Pie pageant, awarded to the nation's best wife and mother. Maxine only has one problem: to win the crown she'll need to find--or build--a family of her own."--provided by publisher.

Time to roll (Roll with it, 2,, 2023)
"When thirteen-year-old Ellie reluctantly agrees to enter a beauty pageant with her best friend Coralee, the director seems determined to feature Ellie and her wheelchair, so she must find a way to participate on her own terms, all while saving her friendship and forming a better relationship with her divorced dad."--

The subway girls (Thorndike Press large print women's fiction, ,, 2018)
"In 1949, dutiful and ambitious Charlotte's dream of a career in advertising is shattered when her father demands she help out with the family business. Meanwhile, Charlotte is swept into the glamorous world of the Miss Subways beauty contest, which promises irresistible opportunities with its Park Avenue luster and local fame status. But when her new friend--the intriguing and gorgeous fellow-participant Rose--does something unforgivable, Charlotte must make a heart-wrenching decision thatwill change the lives of those around her forever. Nearly 70 years later, outspoken advertising executive Olivia is pitching the NYC subways account in a last ditch effort to save her job at an advertising agency. When the charismatic boss she's secretly in love with pits her against her misogynistic nemesis, Olivia's urgent search for the winning strategy leads her to the historic Miss Subways campaign. As the pitch date closes in on her, Olivia finds herself dealing with a broken heart, an unlikely new love interest, and an unexpected personal connection to Miss Subways that could save her job--and her future. The Subway Girls is the charming story of two strong women, a generation apart, who find themselves up against the same eternal struggle to find an impossible balance between love, happiness, and ambition." --

Homicide and halo-halo (Tita Rosie's kitchen mystery, 2,, 2022)
"Death at a beauty pageant turns Tita Rosie's Kitchen upside down in the latest entry of this witty and humorous cozy mystery series by Mia P. Manansala, author of Arsenic and Adobo. Things are heating up for Lila Macapagal. Not in her love life, which she insists on keeping nonexistent despite the attention of two very eligible bachelors. Or her professional life, since she can't bring herself to open her new café after the unpleasantness that occurred a few months ago at her aunt's Filipino restaurant, Tita Rosie's Kitchen. No, things are heating up quite literally, since summer, her least favorite season, has just started. To add to her feelings of sticky unease, Lila's little town of Shady Palms has resurrected the Miss Teen Shady Palms Beauty Pageant, which she won many years ago-a fact that serves as a wedge between Lila and her cousin slash rival, Bernadette. But when the head judge of the pageant is murdered and Bernadette becomes the main suspect, the two must put aside their differences and solve the case-because it looks like one of them might be next"--

Supermodel v luchakh smerti: roman (Chernaiu0361a koshka, ,, 1995)
Description Not Provided

Whiskey and tonic: a Whiskey Mattimoe mystery (Midnight Ink, 2007)
Description Not Provided

The begonia bribe (Wheeler Publishing, 2014)
The Little Miss Begonia Pageant for little girls has decided to hold their event in a Roanoke, Virginia, park. Camellia Harris is called in to help deal with the botanical details, the cute contestants, and their catty mothers. Soon the drama onstage is nothing compared to the judges row. There's jealousy, betrayal, and a love triangle -- which turns deadly when local newsman Telly Stevens is found dead, poisoned by some sort of plant.

All American dream dolls (Milkweed Editions, 1997)
The catty relationship of two black half-sisters in St. Louis. They are Deneen Wilkerson, in her 30s, living by her brains as an ad executive, and body-conscious Clara, a teenager training for a beauty pageant.

Bone appétit (Sarah Booth Delaney mystery, 10,, 2011)
For years, Jitty, Dahlia House's resident ghost, has dreamed that Sarah Booth Delaney would have a child. It looks like Jitty's dream will finally come true, and Sarah Booth is crushed when it doesn't. Depressed, Sarah Booth finally allows her best friend to whisk her away for a luxurious weekend vacation at a special spa and cooking school. The pampering and food go a long way toward making her feel like her old self, but there's another welcome distraction, there's a beauty contest/cook-off going on to find the spa's next spokesperson. It's all great fun until the heated competition boils over, the top contender is poisoned, and the prime suspect hires Sarah Booth to clear her name.